James B. Wyngaarden Oral History Interview, 2005 - Wyngaarden, James B. (2005)
Dr. Wyngaarden speaks about being recruited for the directorship of the National Institutes of Health (NIH); looking back at his chairmanship of the Department of Medicine; important aspects of the department under his chairmanship; Dr. Eugene Stead; the Howard Hughes Medical Institute; his role on the board at the institute; some history of the institute; recruiting Dr. Ralph Snyderman to Duke; Dr. Wyngaarden's commitment to the concept of the physician-scientist; the status of the physician-scientist concept under President Richard Nixon; Dr. Wyngaarden's paper on the physician-scientist and that being the paper most associated with him; changes in the concept of the physician-scientist; role of the general practitioner at Duke; comments on Bayh-Dole and Technology Transfer Act; drug trials; the lack of contribution in genetics from Duke until the current time; the Human Genome Project when he was the director of NIH; his view of Genentech as the director of NIH; Dr. Snyderman's role as chancellor of Duke Medical Center; and Dr. Wyngaarden's continuing work in scientific fields since leaving the NIH.